THE INFLUENCE OF TASK COMPLEXITY AND WORKLOAD ON JOB SATISFACTION AMONG CONTRACT ELEMENTARY SCHOOL TEACHERS IN THE KEMRANJEN SUB-DISTRICT - Yustie, Herawati Anggraeni; Sunarso, Ali (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research examines and analyzes the influence of task complexity and workload on the job satisfaction of non-permanent (contract) elementary school teachers, both partially and simultaneously. The research was conducted on all non-permanent teachers serving in the Kemranjen Sub-district, Banyumas Regency. A quantitative research approach was employed using multiple linear regression analysis. The sampling technique employed was saturated sampling, resulting in a sample of 32 respondents that represented the entire population. Data were collected through questionnaires distributed directly to the respondents. The analysis revealed that task complexity has a negative and significant effect on the job satisfaction of non-permanent teachers, as indicated by a significance value of less than 0.05 and a t-count of -4.245. Conversely, the workload variable did not significantly impact job satisfaction, indicated by a significance value greater than 0.05 and a t-count of 0.987. However, when task complexity and workload were analyzed simultaneously, both variables significantly influenced the job satisfaction of non-permanent elementary school teachers in the Kemranjen Sub-district, contributing 43.1% to the variance explained. These findings suggest that compared to workload, task complexity plays a more significant role in enhancing the job satisfaction of contract teachers. Therefore, the results of this research may serve as a reference for policymakers in designing strategies to improve the well-being and work effectiveness of non-permanent teachers at the elementary school level. These welfare improvement efforts are expected to create a more supportive and productive work environment for non-permanent teachers.